Differential response to acute low dose radiation in primary and immortalized endothelial cells. (October 2013) - Rombouts, Charlotte; Aerts, An; Beck, Michael; De Vos, Winnok H.; Van Oostveldt, Patrick; Benotmane, Mohammed Abderrafi; Baatout, Sarah
Abstract Purpose: The low dose radiation response of primary human umbilical vein endothelial cells (HUVEC) and its immortalized derivative, the EA.hy926 cell line, was evaluated and compared. Material and methods: DNA damage and repair, cell cycle progression, apoptosis and cellular morphology in HUVEC and EA.hy926 were evaluated after exposure to low (0.05–0.5 Gy) and high doses (2 and 5 Gy) of acute X-rays. Results: Subtle, but significant increases in DNA double-strand breaks (DSB) were observed in HUVEC and EA.hy926 30 min after low dose irradiation (0.05 Gy). Compared to high dose irradiation (2 Gy), relatively more DSB/Gy were formed after low dose irradiation. Also, we observed a dose-dependent increase in apoptotic cells, down to 0.5 Gy in HUVEC and 0.1 Gy in EA.hy926 cells. Furthermore, radiation induced significantly more apoptosis in EA.hy926 compared to HUVEC. Conclusions: We demonstrated for the first time that acute low doses of X-rays induce DNA damage and apoptosis in endothelial cells. Our results point to a non-linear dose-response relationship for DSB formation in endothelial cells. Furthermore, the observed difference in radiation-induced apoptosis points to a higher radiosensitivity of EA.hy926 compared to HUVEC, which should be taken into account when using these cells as models for studying the endothelium radiation response.